ORGANIZATIONAL AND GEOGRAPHIC ACCESSIBILITY: OBSTACLES BETWEEN USERS WITH TUBERCULOSIS AND HEALTH SERVICES - Rosana Huppes Engel; Teresinha Heck Weiller; Elaine Miguel Delvivo Farão; Iarema Fabieli Oliveira de Barros; Juliana Bordignon; Emanuelli Mancio Ferreira da Luz (Revista de Enfermagem da Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976928494